Root Hair Adhesion in Posidonia oceanica (L.) Delile Seedlings: A Numerical Modelling Approach - Zenone, Arturo; Filippov, Alexander E.; Kovalev, Alexander; Badalamenti, Fabio; Gorb, Stanislav N. (Frontiers in Mechanical Engineering, 2020)
Animals and plants use adhesion to move, to anchor to a substrate or to disperse seeds and fruits. Some plants developed a root pad as a common strategy to adhere to consolidated substrates.In the marine environment, the seagrass Posidonia oceanica attaches firmly to consolidated substrates via adhesive root hairs forming a pad structure. We used novel morphological and ultrastructural data to develop a numerical model to study the dynamics of root hair adhesion during contact formation on rough consolidated substrates for this species.Morphological analysis, conducted by mean of SEM, highlighted the role of root hair branching in pad formation. TEM microscopy allowed us to identify a glue-like substance at the pad/substrate interface. The numerical model highlighted the role played by the cell wall elasticity in pad formation and its importance in guaranteeing a firm adhesion. Furthermore, the effectiveness of these mechanisms was assessed at different simulated roughness. Increasing knowledge on the adhesion mechanism of seagrass to consolidated substrates could be pivotal to develop advanced seedling-based restoration protocols. The findings of this study can contribute to restoration activities planned to contrast seagrass regression. In particular, transplanting initiatives using seedlings can now better address the search for suitable and low-impacting ways to fix germinated plants to the substrate.